Association between ADCY9 Gene Polymorphisms and Ritodrine Treatment Outcomes in Patients with Preterm Labor - Nari Lee; Ha-Young Yoon; Jin-Young Park; Young-Ju Kim; Han-Sung Hwang; Jeong Yee; Hye-Sun Gwak (MDPI AG, 2021)
The purpose of this study was to investigate the genetic effects of ADCY9 on ritodrine responses in patients with preterm labor. Five single nucleotide polymorphisms (SNPs) of the ADYC9 gene in 163 patients in preterm labor were genotyped: rs879619, rs2601796, rs2531988, rs2531995, and rs2230739. Additionally, rs598961 of the PDE4B gene and rs1042719 of the ADRB2 gene were included for analysis. Patients with CC genotype of ADCY9 rs879619 had a 2.0-fold (95% confidence interval [CI]: 1.3, 3.2) higher hazard of time to delivery than T allele carriers. Patients with combined genotypes of CC in ADCY9 rs879619, AA in PDE4B rs598961, and GC, CC in ADRB2 rs1042719 showed a greater hazard of time to delivery than patients with other combinations (adjusted hazard ratio [AHR] 3.2; 95% CI: 1.7, 6.3), whereas patients carrying the C allele of ADCY9 rs2531995, G allele of PDE4B rs598961, and GG genotype of ADRB2 rs1042719 had a lower hazard of time to delivery than patients carrying other genotypes (AHR 0.4; 95% CI: 0.2, 0.7). Regarding ritodrine-induced adverse drug events (ADEs), height less than 160 cm and CC genotype of ADCY9 rs2531995 showed a greater risk of ADEs. The results of our study suggest that ADCY9 polymorphisms could affect the efficacy and safety of β2-adrenergic agonists.